# Solve the following integral:

$\int {\dfrac{{dx}}{{\sin x + \sin 2x}}} $

Answer

Verified

365.7k+ views

Hint- For solving such problems, try to convert the term in simpler form by the help of trigonometric identities ( sin 2x =2 sin x cos x ) and use substitution method and partial fraction.

To solve the given integral, first solving the denominator

\[\sin x + \sin 2x = \sin x + 2\sin x\cos x = \sin x\left[ {1 + 2\cos x} \right]\]

Now let’s put the fraction together and proceeding further:

\[\dfrac{1}{{\sin x + \sin 2x}} = \dfrac{1}{{\sin x\left[ {1 + 2\cos x} \right]}} = \dfrac{{\sin x}}{{{{\sin }^2}x\left[ {1 + 2\cos x} \right]}}\]

Now we can integrate the above term:

\[\int {\dfrac{{\sin x}}{{{{\sin }^2}x\left[ {1 + 2\cos x} \right]}}dx} \]

Let us consider

\[

u = \cos x \\

du = - \sin xdx \\

{\sin ^2}x = 1 - {\cos ^2}x = 1 - {u^2} \\

\int {\dfrac{1}{{\left( {1 - {u^2}} \right)\left( {1 + 2u} \right)}}} \left( { - du} \right) \\

\int {\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}}} du \\

\]

Now let’s take a break from integration and decompose the expression into partial fractions:

\[\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}} = \dfrac{A}{{\left( {1 + u} \right)}} + \dfrac{B}{{\left( {1 - u} \right)}} + \dfrac{C}{{\left( {1 + 2u} \right)}}\]

Multiplying on both sides \[\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)\]to get rid of denominators. We get:

\[

- 1 = A\left( {1 - u} \right)\left( {1 + 2u} \right) + B\left( {1 + u} \right)\left( {1 + 2u} \right) + C\left( {1 - u} \right)\left( {1 + u} \right) \\

- 1 = A\left( {1 + u - 2{u^2}} \right) + B\left( {1 + 3u + 2{u^2}} \right) + C\left( {1 - {u^2}} \right) \\

- 1 = \left( { - 2A + 2B - C} \right){u^2} + \left( {A + 3B} \right)u + \left( {A + B + C} \right) \\

\]

And now on comparing coefficient from both sides, we have three equations and three variables, so solving further:

\[

0 = - 2A + 2B - C \\

0 = A + 3B \\

-1 = A + B + C \\

\]

Adding all the three equations, we get:

\[

- 1 = 6B \\

B = \dfrac{{ - 1}}{6} \\

\]

From the second equation, we get:

\[A = - 3B = \dfrac{3}{6} = \dfrac{1}{2}\]

From the third equation, we get:

\[C = - 1 - A - B = - 1 - \dfrac{1}{2} + \dfrac{1}{6} = \dfrac{{ - 4}}{3}\]

And so we have:

\[\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}} = \dfrac{1}{{2\left( {1 + u} \right)}} - \dfrac{1}{{6\left( {1 - u} \right)}} - \dfrac{4}{{3\left( {1 + 2u} \right)}}\]

Now we can continue with the integration:

\[

{\text{ = }}\int {\dfrac{1}{{2\left( {1 + u} \right)}}du - \int {\dfrac{1}{{6\left( {1 - u} \right)}}du - \int {\dfrac{4}{{3\left( {1 + 2u} \right)}}du} } } \\

= \dfrac{1}{2}\ln \left| {1 + u} \right| + \dfrac{1}{6}\ln \left| {1 - u} \right| - \dfrac{2}{3}\ln \left| {1 + 2u} \right| + C{\text{ }}\left[ {\because \int {\dfrac{1}{x}dx = \ln x + C} } \right] \\

\]

Now after substituting back the considered value of $u$ we get:

\[{\text{ = }}\dfrac{1}{2}\ln \left| {1 + \cos x} \right| + \dfrac{1}{6}\ln \left| {1 - \cos x} \right| - \dfrac{2}{3}\ln \left| {1 + 2\cos x} \right| + C\]

Note- Integration of some questions as above where direct integration is not possible, solving by the use of partial fraction is very useful. Also sometimes we have to consider some functions like $\sin \& \cos $in terms of some variables, such as $u$ in this case.

To solve the given integral, first solving the denominator

\[\sin x + \sin 2x = \sin x + 2\sin x\cos x = \sin x\left[ {1 + 2\cos x} \right]\]

Now let’s put the fraction together and proceeding further:

\[\dfrac{1}{{\sin x + \sin 2x}} = \dfrac{1}{{\sin x\left[ {1 + 2\cos x} \right]}} = \dfrac{{\sin x}}{{{{\sin }^2}x\left[ {1 + 2\cos x} \right]}}\]

Now we can integrate the above term:

\[\int {\dfrac{{\sin x}}{{{{\sin }^2}x\left[ {1 + 2\cos x} \right]}}dx} \]

Let us consider

\[

u = \cos x \\

du = - \sin xdx \\

{\sin ^2}x = 1 - {\cos ^2}x = 1 - {u^2} \\

\int {\dfrac{1}{{\left( {1 - {u^2}} \right)\left( {1 + 2u} \right)}}} \left( { - du} \right) \\

\int {\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}}} du \\

\]

Now let’s take a break from integration and decompose the expression into partial fractions:

\[\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}} = \dfrac{A}{{\left( {1 + u} \right)}} + \dfrac{B}{{\left( {1 - u} \right)}} + \dfrac{C}{{\left( {1 + 2u} \right)}}\]

Multiplying on both sides \[\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)\]to get rid of denominators. We get:

\[

- 1 = A\left( {1 - u} \right)\left( {1 + 2u} \right) + B\left( {1 + u} \right)\left( {1 + 2u} \right) + C\left( {1 - u} \right)\left( {1 + u} \right) \\

- 1 = A\left( {1 + u - 2{u^2}} \right) + B\left( {1 + 3u + 2{u^2}} \right) + C\left( {1 - {u^2}} \right) \\

- 1 = \left( { - 2A + 2B - C} \right){u^2} + \left( {A + 3B} \right)u + \left( {A + B + C} \right) \\

\]

And now on comparing coefficient from both sides, we have three equations and three variables, so solving further:

\[

0 = - 2A + 2B - C \\

0 = A + 3B \\

-1 = A + B + C \\

\]

Adding all the three equations, we get:

\[

- 1 = 6B \\

B = \dfrac{{ - 1}}{6} \\

\]

From the second equation, we get:

\[A = - 3B = \dfrac{3}{6} = \dfrac{1}{2}\]

From the third equation, we get:

\[C = - 1 - A - B = - 1 - \dfrac{1}{2} + \dfrac{1}{6} = \dfrac{{ - 4}}{3}\]

And so we have:

\[\dfrac{{ - 1}}{{\left( {1 - u} \right)\left( {1 + u} \right)\left( {1 + 2u} \right)}} = \dfrac{1}{{2\left( {1 + u} \right)}} - \dfrac{1}{{6\left( {1 - u} \right)}} - \dfrac{4}{{3\left( {1 + 2u} \right)}}\]

Now we can continue with the integration:

\[

{\text{ = }}\int {\dfrac{1}{{2\left( {1 + u} \right)}}du - \int {\dfrac{1}{{6\left( {1 - u} \right)}}du - \int {\dfrac{4}{{3\left( {1 + 2u} \right)}}du} } } \\

= \dfrac{1}{2}\ln \left| {1 + u} \right| + \dfrac{1}{6}\ln \left| {1 - u} \right| - \dfrac{2}{3}\ln \left| {1 + 2u} \right| + C{\text{ }}\left[ {\because \int {\dfrac{1}{x}dx = \ln x + C} } \right] \\

\]

Now after substituting back the considered value of $u$ we get:

\[{\text{ = }}\dfrac{1}{2}\ln \left| {1 + \cos x} \right| + \dfrac{1}{6}\ln \left| {1 - \cos x} \right| - \dfrac{2}{3}\ln \left| {1 + 2\cos x} \right| + C\]

Note- Integration of some questions as above where direct integration is not possible, solving by the use of partial fraction is very useful. Also sometimes we have to consider some functions like $\sin \& \cos $in terms of some variables, such as $u$ in this case.

Last updated date: 01st Oct 2023

•

Total views: 365.7k

•

Views today: 5.65k

Recently Updated Pages

What is the Full Form of DNA and RNA

What are the Difference Between Acute and Chronic Disease

Difference Between Communicable and Non-Communicable

What is Nutrition Explain Diff Type of Nutrition ?

What is the Function of Digestive Enzymes

What is the Full Form of 1.DPT 2.DDT 3.BCG

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

One cusec is equal to how many liters class 8 maths CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE